2014
DOI: 10.3897/zookeys.401.7299
|View full text |Cite
|
Sign up to set email alerts
|

A review of the Nearctic genus Prostoia (Ricker) (Plecoptera, Nemouridae), with the description of a new species and a surprising range extension for P. hallasi Kondratieff & Kirchner

Abstract: The Nearctic genus Prostoia (Plecoptera: Nemouridae) is reviewed. Prostoia ozarkensis sp. n. is described from the male and female adult stages mainly from the Interior Highland region encompassing portions of Arkansas, Missouri, and Oklahoma. Prostoia ozarkensis sp. n. appears most closely related to two species, one distributed broadly across the western Nearctic region, P. besametsa (Ricker), and one found widely throughout the central and eastern Nearctic regions, P. completa (Walker). A surprising range e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 12 publications
0
4
0
Order By: Relevance
“…Several genera of the Nemouridae family have distinct disjunctions in their distribution [15]. For example, Ostrocerca Ricker, 1952, Prostoia Ricker, 1952 and Soyedina Ricker, 1952 were found in both the extreme western and the extreme eastern regions of North America, but they were absent in the central area [17], [18]. Similar disjunctive distributions were also observed among Protonemura , Indonemoura , Sphaeronemoura Shimizu & Sivec, 2001, and Illiesonemoura Baumann, 1975 in the Palaearctic region [19], the western and eastern Himalayan ranges [20] and North and South India [15].…”
Section: Introductionmentioning
confidence: 99%
“…Several genera of the Nemouridae family have distinct disjunctions in their distribution [15]. For example, Ostrocerca Ricker, 1952, Prostoia Ricker, 1952 and Soyedina Ricker, 1952 were found in both the extreme western and the extreme eastern regions of North America, but they were absent in the central area [17], [18]. Similar disjunctive distributions were also observed among Protonemura , Indonemoura , Sphaeronemoura Shimizu & Sivec, 2001, and Illiesonemoura Baumann, 1975 in the Palaearctic region [19], the western and eastern Himalayan ranges [20] and North and South India [15].…”
Section: Introductionmentioning
confidence: 99%
“…Ostrocerca truncata (Claassen, 1923) can be a locally abundant species in headwater streams, is distributed extensively along the Appalachian Mountains (DeWalt et al 2017), and has been reported <100 km northward in DeSoto State Park (DeKalb County; Young et al 1989). A second species, Prostoia completa (Walker, 1852), is typically found in small rivers and large streams through eastern and central North America (Grubbs et al 2014) and was plotted in James (1972, her Fig. 126) from southern Tallapoosa County.…”
Section: Resultsmentioning
confidence: 99%
“…material 1). These include faunal lists and analyses of species richness patterns for the state as a whole or a subset (DeWalt et al 2012, Gaufin 1956, Grubbs et al 2013b, Tkac 1979, Walker 1947), records of taxa from a single stream (Beckett 1987, Tkac and Foote 1978, Robertson 1984, Robertson 1979, Fishbeck 1987), discussion of morphological features or genetic diversity for one or more species (Clark 1934, Yasick et al 2007, Yasick et al 2015), or included records of Ohio species from descriptions or revisionary or other works (Baumann 1974, Frison 1942, Fullington and Stewart 1980, Grubbs 2006, Grubbs 2015, Grubbs and DeWalt 2008, Grubbs and DeWalt 2012, Grubbs and Stark 2001, Grubbs et al 2014, Grubbs et al 2013c, Kondratieff 2004, Kondratieff and Kirchner 1993, Kondratieff and Kirchner 2009, Kondratieff et al 1988, Nelson 2000, Ricker 1952, Ricker and Ross 1968, Ricker and Ross 1969, Ross and Ricker 1964, Ross and Ricker 1971, Ross and Yamamoto 1967, Ross et al 1967, Stark 1986, Stark 1989, Stark 2000, Stark 2004, Stark and Baumann 1978, Stark and Baumann 2004, Stark and Gaufin 1974, Stark and Gaufin 1976, Stark and Kondratieff 2010, Stark and Kondratieff 2012, Stark et al 1988, Stewart 2000, Surdick 2004, Szczytko and Kondratieff 2015, Szczytko and Stewart 1978, Szczytko and Stewart 1981, Young et al 1989, Zwick 1971). …”
Section: Resultsmentioning
confidence: 99%